Complement activation in neonatal infection. Issue 7 (July 1992) - Peakman, M; Senaldi, G; Liossis, G; Gamsu, H R; Vergani, D
Abstract : To investigate the usefulness of indices of complement activation in the diagnosis of infections in the neonatal period, activation products C4d, Ba, and C3d were measured in 42 babies with a putative diagnosis of infection based on clinical/laboratory criteria, and compared with conventional clinical and haematological criteria of infection and with C reactive protein. The diagnosis of sepsis was confirmed by culture and identification of organisms in 17. Fourteen babies in whom infection was not suspected formed the control group. In babies with proved infection, concentrations of the fragments C4d, Ba, and C3d were higher than in babies with suspected infection in whom microbiological tests were negative, and concentrations of Ba and C3d were higher than in controls. C reactive protein and the platelet count were not significantly different in babies with proved infection and those with negative microbiological tests, but in the latter, C reactive protein concentrations were higher than in controls. Of the indices studied, high concentrations of Ba predicted microbiologically proved infection with the highest sensitivity (47.1%) and specificity (92.0%). Ba thus seems to be useful as an early indicator of infection in the neonatal period.